Does potentially mineralizable nitrogen predict maize yield in newly cropped soil?. Issue 1 (11th April 2020) - Gebremedhin, Maheteme; Sarr, Sait; Coyne, Mark; Freytag, Ann; Sistani, Karamat R.
Abstract: Fallow soils converted to crop use have unpredictable soil organic nitrogen (SON) availability during the growing season, which incentivizes over‐applying fertilizer N by way of compensation. Potentially mineralizable nitrogen (PMN) is a soil health indicator, and its increase is a management strategy to meet crop N demands. How well does PMN predict yield in transition, periods from fallow to crop, especially when conservation practices are imposed simultaneously? In a short‐term study, conducted in Madison County, Kentucky (37.85 N, 84.29 W) from 2015 to 2017, we tested the hypothesis that implementing conservation practices (use of cover crops and manure) during the transition period would mitigate adverse effects on N availability by increasing PMN and significantly benefit maize ( Zea mays L.) grain yield. Six treatments were used: (a) an unamended control; (b) cover crops; (c) horse manure; (d) cover crops and horse manure; (e) chemical fertilizer; and (f) cover crops and chemical fertilizer. Soils were sampled after cover crop termination, before manure or fertilizer application in spring, and at fall harvest each year and analyzed for PMN. The seasonal PMN and maize grain yield were influenced by cover crops and manure ( p < .05). Maize grain yield had a positive response to cover crops but not manure. The correlation between PMN and grain yield, though positive, was very weak ( R 2 = .03). We conclude that conservation practices, particularly cover crops, in the transition period can benefit PMN and crop yield, but PMN is not a good predictor of yield during transition stages.